Reagent controlled stereoselective synthesis of teichoic acid α-(1, 2)-glucans. Issue 11 (6th March 2020) - Wang, Liming; Berni, Francesca; Enotarpi, Jacopo; Overkleeft, Hermen S.; van der Marel, Gijs; Codée, Jeroen D. C.
Abstract : Additive controlled glycosylation reactions are used for the construction of α-(1, 2)-glucosidic linkages, such as those featuring in E. faecalis lipoteichoic acid. Abstract : The stereoselective construction of 1, 2- cis -glycosidic linkages is key in the assembly of biologically relevant glycans, but remains a synthetic challenge. Reagent-controlled glycosylation methodologies, in which external nucleophiles are employed to modulate the reactivity of the glycosylation system, have become powerful means for the construction of 1, 2- cis -glycosidic linkages. Here we establish that nucleophilic additives can support the construction of α-1, 2-glucans, and apply our findings in the construction of a d -alanine kojibiose functionalized glycerol phosphate teichoic acid fragment. This latter molecule can be found in the cell wall of the opportunistic Gram-positive bacterium, Enterococcus faecalis and represents a structural element that can possibly be used in the development of therapeutic vaccines and diagnostic tools.